Interrogating the lack of diversity of thought in the pandemic response that led to mistakes - holistic evidence-based approach to deal with future pandemics - Colleen Aldous; Hendrik G. Kruger (Frontiers Media S.A., 2023)
The COVID-19 pandemic, triggered by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), rapidly became a worldwide emergency. How it was managed garnered both commendation and vehement censure. This crisis profoundly affected healthcare, the economy, education, and public confidence in scientific endeavors. Our primary aim was to scrutinize the shortcomings in the pandemic management and to articulate a more effective strategy for handling prospective pandemics. We delved into the errors encountered in the COVID-19 response and posited a holistic, evidence-grounded approach for future pandemic mitigation.